2020
DOI: 10.1002/adhm.202000208
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of Bioinspired Biomaterials for Tissue Regeneration

Abstract: Biological systems, which possess remarkable functions and excellent properties, are gradually becoming a source of inspiration for the fabrication of advanced tissue regeneration biomaterials due to their hierarchical structures and novel compositions. It would be meaningful to learn and transfer the characteristics of creatures to biomaterials design. However, traditional strategies cannot satisfy the design requirements of the complicated bioinspired materials for tissue regeneration. 3D printing, as a rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 165 publications
0
31
0
2
Order By: Relevance
“…Studies indicated that it could function like a human lung, by displaying its ability to mix oxygen with Red blood cells (RBC) when the air sac was ventilated with O 2 . 95,96 Recently, 3D self-organized tissues structures (organoids) that mimic the structural, chemical and physiological characteristics of organs are being developed in vitro as a promising approach for tissue regeneration. 97 These organoids are obtained from various cells like embryonic stem cells (ESCs), induced pluripotent stem cells (iPSCs) and adult stem cells.…”
Section: 13) Extra Cellular Matrixmentioning
confidence: 99%
“…Studies indicated that it could function like a human lung, by displaying its ability to mix oxygen with Red blood cells (RBC) when the air sac was ventilated with O 2 . 95,96 Recently, 3D self-organized tissues structures (organoids) that mimic the structural, chemical and physiological characteristics of organs are being developed in vitro as a promising approach for tissue regeneration. 97 These organoids are obtained from various cells like embryonic stem cells (ESCs), induced pluripotent stem cells (iPSCs) and adult stem cells.…”
Section: 13) Extra Cellular Matrixmentioning
confidence: 99%
“…Future fabrication of bio-inspired hydrogels would be involved with multi-material 3D bioprinting, which provides the ability Figure 4. The future outlook of 3D bioprinting for fabrication of bio-inspired tissues for tissue engineering applications [82].…”
Section: Future Outlookmentioning
confidence: 99%
“…However, the 1990s supposed the true growth of the technique with the development of the 3D printers of industrial grade in 1990, and 1993 was the year in which Solidscape developed their dot-on-dot 3D printing technique. This technique integrated the use of polymer-jet fabrication with high precision models, opening new application horizons for the technique like regenerative medicine [ 103 ]. The first biomedical use of 3D printing dates back to 1999, and since then, the number of studies relating 3D printing and biomedicine have shown an exponential growth.…”
Section: 3d Printingmentioning
confidence: 99%
“…Thus, different printing technologies, such as inkjet-based bioprinting, stereolithography bioprinting and magnetic bioprinting, have been used, achieving the successful development of various complex tissues such as bone, cartilage, skin, heart and lung [ 103 , 110 ]. In this context, Rathan et al investigated the use of scaffolds made up of a 3D printed PCL frame that has blinks with MSC, grow factors and a hydrogel.…”
Section: 3d Printingmentioning
confidence: 99%
See 1 more Smart Citation